Carotid Endarterectomy with Intermediate Cervical Plexus Block - Barone, Marco (Texas Heart Institute, 2010)
During carotid endarterectomy, the use of locoregional anesthesia to achieve a combined superficial and deep cervical plexus block can cause cardiovascular, respiratory, and neurologic complications. Seeking to reduce risk and find an easier procedure, we applied locoregional anesthesia and an intermediate cervical plexus block in a series of patients who underwent carotid endarterectomy. From 2006 through 2007, 183 patients underwent primary carotid endarterectomy at our hospital. Mean age was 75.9 ± 9.9 yr; mean body mass index, 27.3 ± 6.7 kg/m2; and median American Society of Anesthesiologists physical status classification, P3 (range, P2–P4). All procedures combined an intermediate cervical plexus block with subcutaneous infiltration of the incision line. We inserted a 15-mm, 25G needle to its full length, perpendicular to the skin along the posterior border of the sternocleidomastoid muscle, midway between the mastoid process and the clavicle. We injected 10 mL of 0.75% ropivacaine solution for 3 to 5 minutes. This block was systematically combined with subcutaneous infiltration of the incision line with the ropivacaine (0.75%, 10 mL), and sometimes also with 2% topical lidocaine intraoperatively. If necessary, intraoperative sedation, analgesia, or both were given to patients to improve their compliance. Intraoperative topical lidocaine was required in 59 patients (32.2%), and intravenous midazolam, fentanyl, or both were required in 29 patients (15.8%). Two procedures were converted to general anesthesia (1.1%). No perioperative deaths or complications occurred. Postoperatively, 2 patients experienced strokes and 1 sustained a myocardial infarction (total rate, 1.6%). We found the intermediate cervical plexus block to be feasible, effective, and safe, with low perioperative and postoperative complication rates. Herein, we report our findings.